Aromatic stabilization in heterofullerenes C48X12 (X = N, P, B, Si) - Chen, Zhongfang; Jiao, Haijun; Moran, Damian M.; Hirsch, Andreas; Thiel, Walter; Schleyer, Paul (Journal of Physical Organic Chemistry, 2003)
B3LYP density functional calculations were performed on two S symmetrical isomers (I and II) of CX (X = N, B, P, Si) heterofullerenes, and their global and local aromaticity were evaluated by nucleus-independent chemical shifts (NICS). Despite the unfavorable heteroatom repulsive interactions, isomer II is more stable than I owing to the combination of global and local aromaticity. The latter arises from the presence of triphenylene units in isomer II. The aromatic stabilization effects found in this study should be taken into account when predicting the most stable isomers of heterofullerenes. The same is true for predictions of the isomers of fullerene adducts such as CCl. Copyright © 2003 John Wiley & Sons, Ltd.